HUBUNGAN TERPAAN IKLAN BUKALAPAK DI SCTV DENGAN MINAT BELI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS SEBELAS MARET SURAKARTA ANGKATAN 2014 - Purnama, Aji Setya; Siswanta, Bedjo Sukarno, (Solidaritas, 2017)
BELI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS SEBELAS MARET SURAKARTA ANGKATAN 2014Oleh:Aji Setya Purnama, Bedjo Sukarno, SiswantaÂ Â ABSTRACTÂ Bukalapak is one of e-commerce sites in Indonesia. One of the marketing techniques by Bukalapak is advertise their product using television. Attractive ads can increase the buying interest of audiences who see that ad. The purpose of this study is to determine the positive and significant relations of Bukalapak advertisement exposure on SCTV with the buying interestâs students of Communication Studies Universitas Sebelas Maret Surakarta in the 2014 academic year. This research is a quantitative research and used 54 students as a sample. The technique of analysis data used Rank Spearman correlation formula. The result is value of correlation coeficient is about 0,664 > 0,2681. Hypothesis which states: There is positive and significant relations between Bukalapak advertisement exposure on SCTV with the buying interestâs students of Communication Studies Sebelas Maret University Surakarta in the 2014 academic year.